2014
DOI: 10.1128/aac.02445-13
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Clinical Outcomes of Patients with Carbapenem-Resistant Klebsiella pneumoniae Bacteriuria

Abstract: Carbapenem-resistant Klebsiella pneumoniae (CRKP) bacteriuria is a frequently encountered clinical condition, but its clinical impact is unknown. We conducted a retrospective cohort study to define the epidemiology and outcomes for patients with CRKP bacteriuria. Patients with positive urine cultures for CRKP were classified as having asymptomatic bacteriuria (ASB) or symptomatic urinary tract infection (UTI). Among 105 patients with CRKP bacteriuria, 80% (84/105 patients) and 20% (21/105 patients) had ASB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 25 publications
2
31
0
4
Order By: Relevance
“…This is consistent with our findings that medical history showing surgery, hospitalization, antibiotic use prior to infection, and the presence of invasive medical devices at the moment of infection were associated with CR-Kp acquisition (Table 1). Meanwhile, we found an overall 34% mortality rate, in accordance with previous reports of rates that varied from 6% to 60% depending on the severity of infection (9,42,(68)(69)(70). Interestingly, our study revealed a highly heterogeneous genetic background of CR-Kp strains, and CR-Kp from different clones displayed distinct clinical characteristics in our local epidemiology.…”
Section: Discussionsupporting
confidence: 79%
“…This is consistent with our findings that medical history showing surgery, hospitalization, antibiotic use prior to infection, and the presence of invasive medical devices at the moment of infection were associated with CR-Kp acquisition (Table 1). Meanwhile, we found an overall 34% mortality rate, in accordance with previous reports of rates that varied from 6% to 60% depending on the severity of infection (9,42,(68)(69)(70). Interestingly, our study revealed a highly heterogeneous genetic background of CR-Kp strains, and CR-Kp from different clones displayed distinct clinical characteristics in our local epidemiology.…”
Section: Discussionsupporting
confidence: 79%
“…Unfortunately, other investigations into CRKP among OTRs excluded UTIs (7)(8)(9)(10). Still others included both OTRs and nontransplant patients but focused on a particular therapy (11), bacteremia (12,13), or factors associated with the development of UTIs among patients with asymptomatic bacteriuria (14). Extrapolating from data for nontransplant patients is problematic.…”
Section: Discussionmentioning
confidence: 99%
“…Mortality rates ranged from 0 to 33%. Finally, in a recent study of patients from the United States, there were 11 OTRs with UTIs due to CRKP (14). While detailed clinical characterizations were not provided, multivariate logistic regression analyses identified solid organ transplantation as independently associated with UTI among all patients with CRKP bacteriuria (OR, 4.50 [95% CI, 1.39 to 14.52]).…”
Section: Discussionmentioning
confidence: 99%
“…85 Doxycycline and, to a lesser extent, minocycline retain activity against KPC-producing K. pneumoniae and have been used successfully in the treatment of urinary tract infection. 86,87 Limited in vitro data suggest that isolates with a doxycycline MICs close to the susceptibility breakpoint may not be inhibited well by this agent, 88 and that doxycycline may have some synergy with gentamicin for KPC-producing K. pneumoniae , but synergy with other commonly used drugs (e.g., colistin) is not robust. Therefore, its potential use is likely limited to therapy of urinary tract infection in patients who are not systemically ill.…”
Section: Antimicrobial Agents Used For Treatment Of Cpe Infectionsmentioning
confidence: 99%